Computational methods for nonlinear dynamical systems : theory and applications in aerospace engineering /: theory and applications in aerospace engineering. (2022) - Wang, Xuechuan; Yue, Xiaokui; Dai, Honghua; Feng, Haoyang; Atluri, Satya N
No abstract available